2014
DOI: 10.1074/jbc.m114.581801
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Misfolded Region in Superoxide Dismutase 1 That Is Exposed in Amyotrophic Lateral Sclerosis

Abstract: Background: Misfolded SOD1 is associated with sporadic and familial ALS. Results: The epitope of C4F6, an antibody specific for misfolded SOD1, has been defined. Loops IV and VII in SOD1 modulate exposure of this epitope. Conclusion: Exposure of the C4F6 epitope correlates with heightened SOD1-mediated toxicity. Significance: Concealing the C4F6 epitope by stabilizing SOD1 loops IV and VII has therapeutic potential for ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…These small, soluble oligomers undergo aberrant interactions with cell machinery and activate cell death pathways, but their exact stoichiometry is not known and their properties have yet to be characterized. Recently, metastable soluble Cu,Zn superoxide dismutase (SOD1) oligomers have been identified that contain an epitope associated with disease-linked species of SOD1, mutants of which are implicated in a subset of ALS (15)(16)(17)(18). Size exclusion chromatography (SEC) of these oligomers revealed a size range of two to four monomers, consistent with previous findings of potentially cytotoxic SOD1 oligomers (19)(20)(21).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…These small, soluble oligomers undergo aberrant interactions with cell machinery and activate cell death pathways, but their exact stoichiometry is not known and their properties have yet to be characterized. Recently, metastable soluble Cu,Zn superoxide dismutase (SOD1) oligomers have been identified that contain an epitope associated with disease-linked species of SOD1, mutants of which are implicated in a subset of ALS (15)(16)(17)(18). Size exclusion chromatography (SEC) of these oligomers revealed a size range of two to four monomers, consistent with previous findings of potentially cytotoxic SOD1 oligomers (19)(20)(21).…”
supporting
confidence: 81%
“…Instead, residues comprising the SOD1 dimer interface are spread into discrete regions on each monomer, with a significant fraction solvent-exposed in the SOD1 trimer (Movie S2). Additionally, the recently discovered epitope of the C4F6 Ab (18), which preferentially binds the SOD1 trimer (Fig. S4A) as well as several other disease-linked SOD1 species (15,16) over the native dimer or monomer, is completely exposed on the surface of the trimer structure ( Fig.…”
Section: Sod1 Trimer Features Nonnative Secondary Tertiary and Quatmentioning
confidence: 99%
“…Furthermore, we find strong correlations within the zinc-binding loop (residues 49–60) only in A4V–SOD1, whereas in WT-, T2D-, and T2D/A4V–SOD1 these correlated motions are suppressed (Figure S6). The zinc-binding loop has been suggested to allosterically regulate the conformation of the C4F6 epitope (Bosco et al, 2010), which is directly linked to neural-toxicity of SOD1 in a primary microglia activation assay (Furukawa et al, 2015; Rotunno et al, 2014). We propose that in A4V–SOD1 the cross-correlated motions promote the exposure of the disease-related epitope, and that the T2D/A4V double mutant prevents this effect.…”
Section: Resultsmentioning
confidence: 99%
“…S4), and the fact that similar m values were determined for all PFN1 variants by the urea denaturation analysis suggested these proteins adopt similar tertiary structures as well (Table 1) (18). To probe further for potential structural differences between PFN1 WT and ALS-linked variants, these proteins were subjected to native gel electrophoresis, a biochemical technique capable of detecting conformational differences between misfolded variants and their WT counterparts (19). PFN1 WT and E117G migrated predominately as single, distinct bands with similar mobility, whereas multiple bands of slower mobility were observed for PFN1 variants C71G, M114T, and G118V (Fig.…”
Section: Als-linked Mutations Induce a Misfolded Conformation Within mentioning
confidence: 99%